A proposed Design and Implementation for Securely Storing Medical Records: A Review - Shahanas Rameez,; Athulya Raj T,; Muhammed Nishan C,; Salmanul Faris M H,; Teena James, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Data security and integrity have become critical concerns in the healthcare industry, where the management of sensitive medical information demands robust and innovative solutions. With the increasing digitization of medical records and the need for remote access, it is imperative to develop secure systems that address privacy concerns and prevent unauthorized access. This paper introduces a decentralized framework lever- aging blockchain technology, specifically Ethereum, integrated with the Interplanetary File System (IPFS), to provide secure, scalable, and transparent storage solutions for patient data. The proposed approach shifts ownership of medical records to patients, enabling them to have full control over access and sharing permissions through a secure, patient-centric model. The system also incorporates a unified digital wallet for storing med- ical credentials and records, offering convenience and enhanced security. A comprehensive implementation plan is presented, highlighting steps for development, adoption, and deployment across healthcare networks. Evaluation metrics and feedback mechanisms are also proposed to ensure system performance, user satisfaction, and continuous improvement. Additionally, potential applications, such as incentivized health monitoring and interoperability with existing healthcare systems, are explored. This framework aims to revolutionize healthcare data manage- ment by addressing challenges related to scalability, privacy, and accessibility, ultimately contributing to a more secure and efficient global healthcare ecosystem.
Keywords: Ethereum; BlockChain; Decentralized; IPFS